Մրգահատապտղային էքստրակտների օգտագործումը ֆունկցիոնալ նշանակության ըմպելիքների ստացման նպատակով - Յավրույան, Ն. Վ.; Կարապետյան, Վ. Ա. (ՀԱԱՀ հիմնադրամ)
Հետազոտությունների հիման վրա մշակվել են խաղողի անմիջապես մամլված հյութից և ֆեյխոայի ու մոշի էքստրակտներից ստացվող նոր ֆունկցիոնալ ըմպելիքների բաղադրատոմսեր: Որոշվել են բնական հումքից կենսաբանական ակտիվ նյութերի արդյունահանման մեթոդի (էքստրակցիայի միջոցով) օպտիմալ պարամետրերը և ռեժիմները: Վիտամինների, հանքանյութերի, մակրո- և միկրոտարրերի զգալի պարունակության շնորհիվ նոր տեսակի խմիչքները ձեռք են բերել բարձր զգայաբանական ու ֆունկցիոնալ հատկություններ, ուստի առաջարկվում է իրականացնել դրանց սերիական արտադրություն։ На основе исследований обоснованы и разработаны рецепты новых функциональных напитков, получаемых из виноградного сока прямого отжима армянского сорта Хндогни и экстрактов фейхоа и ежевики. Определены оптимальные параметры и режимы метода выделения биологически активных веществ из природного сырья (экстракции). Благодаря значительному содержанию витаминов, минералов, макро- и микроэлементов новые виды напитков приобрели высокие органолептические и функциональные свойства, следовательно рекомендуется их внедрение в производство. Drinks saturated with biologically active substances can be obtained from non-alcoholic drinks or mixed berry juices. Natural plant materials were used as a source of physiologically valuable food components: citrus, stone fruits, berries, medicinal herbs, etc. We have developed new functional drink recipes based on directly pressed grape juice and natural raw materials rich in organic acids, vitamins, minerals, and other macro-elements and micro-elements such as feijoa, and blackberry. The Armenian Khndoghn grape variety was chosen to produce juices with the first pressing. This juice has a high biological value and harmonious taste with aromatic compounds. Three drinks were prepared, each containing grape juice and blackberry juice in 80:20, 90:10, and 70:30 ratios. Based on the results, optimal parameters and methods for extracting biologically active substances from plant raw materials (by extraction) were determined, and their organoleptic and dietary properties were improved. Due to the high content of vitamins, phenolic carbonic, organic acids, macro-elements, and micro-elements, new drinks have acquired excellent sensory and functional properties, so including them in serial production is recommended.
Keywords: Սննդագիտություն և տեխնոլոգիա